Labour law as an object of juridical-penal protection - Cifuentes Dávila, Jhean Franco (2022)
Our work refers to the need to establish whether there is an adequate criminal policy in Peru that ensures sufficient protection of the right of association and freedom of work in conditions of equality, justice and equity. It seeks to establish whether, in the classification of the various manifestations of action which violate or endanger the "freedom of work", the Peruvian legislator has complied with an adequate criminalization process, which prevents us from the possibility of defects in the typical adaptation or that generates concurrence areas that make criminal prosecution difficult.